AN ANALYSIS OF STUDENTS’ DIFFICULTIES IN READING COMPREHENSION AT SMA NEGERI 1 SUKODADI LAMONGAN - Prihatini, Sulih Okta (E-Link Journal, 2020)
Reading is one of the four language skills taught in the English language learning process besides listening, speaking, and writing. This research aims to know the students’ difficulties in reading comprehension at SMA Negeri 1 Sukodadi and to know the factors of students’ difficulties in reading comprehension at SMA Negeri 1 Sukodadi. This research is descriptive qualitative research. The research was conducted in march 2020. The subject of research was the tenth-grade MIPA 5 of SMA Negeri 1 Sukodadi who were detected that they had difficulties in reading comprehension. The techniques for collecting the data were interviews and documents. the researcher collected the data such as students’ worksheet. The second was data reduction. The researcher classified and reduced the data based on focus. The researcher deleted several data that did not relate to the difficulties in reading comprehension. The third was the data display, the researcher arranged the information to conclude. The researcher presented the data from the difficulties in reading comprehension, and the last is the conclusion. The result of the research showed that some students had difficulties in reading comprehension and they had difficulty in different levels, namely literal comprehension, inferential comprehension, critical comprehension, and creative comprehension. The most difficulties experienced by students were at the level of creative comprehension. The factor of the students’ difficulties in comprehension at tenth grade, there was an inadequate instruction presented by the teacher, lack of pupils’ interest, and the vocabulary difficulties.